The Quality of Life Level in Female Patients with Fibromyalgia Syndrome and the Associated Factors - Aliye Bulut; Emel Top (Galenos Yayinevi, 2018)
Objective: In our study, we were examined the quality of life and its relationship with socio-demographic characteristics in female patients with Fibromyalgia syndrome (FMS) who applied to outpatient clinic. Materials and Methods: In the study, 108 female patients applying to physical therapy outpatient clinic between May 1, 2017 and September 1, 2017, and diagnosed with FMS were included. The data collection tool used in the study was the questionnaire developed by the researcher based on the literature information. The questionnaire consisted of two parts. The first part of the form consisted of the question set querying the socio-demographic characteristics (15 questions), and the second part consisted of the quality of life bref scale used to assess the quality of life of the cases. Results: When the quality of life scores of the individuals according to their economic status were examined; the emotional role functioning, physical functioning, physical role functioning, and physical indicator scores of individuals with middle income level were significantly higher than other income groups (p<0.05). Conclusion: Consequently, we can say that the quality of life is better in female patients who have a high income level with education, normal body mass index, regular sleeping and diagnosis of fibromyalgia.